Pengaruh Pemberian Aromaterapi Lavender terhadap Peningkatan Kualitas Tidur Ibu Hamil Trimester III - Lathifatun Nafsiyah; Kamidah Kamidah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: Sleep disturbances are common in third-trimester pregnant women and are a major trigger for poor sleep quality, which can lead to complications in pregnancy, delivery, and for the unborn baby. Poor sleep quality can be addressed through non-pharmacological methods, such as lavender aromatherapy, which contains linalool acetate that can provide relaxation and improve sleep quality in third-trimester pregnant women. Objective: This study aims to determine the effect of lavender aromatherapy on improving sleep quality in third-trimester pregnant women. Method: The research design is a pre-experimental design with a pre-test post-test design. Samples were taken using consecutive sampling, with a total of 23 third-trimester pregnant women. This study used lavender aromatherapy with a reed diffuser at night before bed for 7 days. The Pittsburgh Sleep Quality Index (PSQI), which consists of seven components, was used as the sleep quality instrument. Data analysis was performed using the Wilcoxon test. Results: Based on the Wilcoxon test results, a P-value of 0.000 was obtained, which is <0.05, indicating that Ha is accepted, meaning there is an effect of lavender aromatherapy on improving sleep quality in third-trimester pregnant women. 22 out of 23 respondents (95.7%) showed improvement in sleep quality. Conclusion: There is an effect of lavender aromatherapy on improving sleep quality in third-trimester pregnant women.